COMPARATIVE ASSESSMENT OF THE EFFICACY OF ADDITIONAL ENDOTHELIAL-PROTECTIVE THERAPY IN PATIENTS WITH CORONARY HEART DISEASE - Kuzminova, N.V.; Romanova, V.O.; Sierkova, V.K.; Lukyantseva, H.V.; Osovska, N.Yu.; Knyazkova, I.I.; Havrylyuk, A.O.; Marchak, T.V. (World of Medicine and Biology, 2019)
To study the efficacy of additional appointment of endothelial-protective therapy, depending on the variant of coronary heart disease (CHD) course, 43 patients were examined. All subjects additionally to standard basic therapy received a fixed combination of meldonium (180 mg) with gamma-butyrobetaine (60 mg) orally 2 capsules twice daily for 4 weeks. Depending on the CHD variant patients were divided into 2 groups. The first group (n=22) included patients with stable CHD course, the second group (n=21) was consisted from patients with unstable angina. The parameters were evaluated before the prescription of therapy and 1 month after its initiation. Complex treatment (basic therapy plus fixed combination of meldonium with gamma-butyrobetaine) resulted in a significant (p